The color on the walls of the cells of the monastery of Santa Catalina de Siena in Arequipa - Velazco Gutiérrez, Marisol (2023)
The present work studies the color applied with lime paint on the walls of cells or homes of the nuns of the Monastery of Santa Catalina of Arequipa, where different layers of color or chromatic stratigraphy are preserved, which are a direct source to determine technical characteristics and significance. contextual. The tradition of painting lime ashlar walls with indigo blue, yellow ocher, red ocher, orange ocher and white corresponds to a technique and aesthetic that has remained intact for more than 400 years. The methodology began with the identification of layers of colors on the interior and exterior walls that characterize this unique work of art; For this purpose, coves or exploration windows were used, a chromatic and architectural survey detailed in cards. Subsequently, the technical characteristics were evaluated, preparing color samples on ashlar supports with lime paint obtained for the maintenance of the monastery, thus studying materials, preparation and application. The contextual significance of color was studied through tables that show the colors used on the interior and exterior walls of the rooms, which allowed us to appreciate the reduced palette of colors, the contrasts, the relationship with the uses of the space and with the formal characteristics of the space. urban complex of Arequipa viceregal architecture.